Robotic process automation: assessment of the technology for transformation of business processes. (18th July 2019) - Dey, Sourav; Das, Arindam
We examine how robotic process automation (RPA) can be deployed as a technology solution in business processes and services as a transformation lever beyond traditional business process management and outsourcing. RPA is a new breed of software that allows for enterprise-wide automation of repetitive business processes, with the promise of potential FTE savings, better service quality and improved service delivery. Through an extensive survey of practitioners involved with RPA, this exploratory research identifies the motivation and challenges of RPA implementation as envisaged by the user communities. We also find the complementary perspectives of RPA product development communities. Consequently, we recommend ways to align the perspectives of the user communities and the developer communities to enable definitive value creation for the organisations. The findings and recommendations would help practitioners who develop RPA products or adopt these products in their IT ecosystems.